Acanthamoeba S13WT relies on its bacterial endosymbiont to backpack human pathogenic bacteria and resist Legionella infection on solid media. Issue 3 (16th April 2018) - Okubo, Torahiko; Matsushita, Mizue; Nakamura, Shinji; Matsuo, Junji; Nagai, Hiroki; Yamaguchi, Hiroyuki
Summary: Soil‐borne amoeba Acanthamoeba S13WT has an endosymbiotic relationship with an environmental Neochlamydia bacterial strain. However, regardless of extensive experiments in liquid media, the biological advantage of the symbiosis remained elusive. We therefore explored the role of the endosymbiont in predator‐prey interactions on solid media. A mixed culture of the symbiotic or aposymbiotic amoebae and GFP‐expressing Escherichia coli or Salmonella Enteritidis was spotted onto the centre of a LB or B‐CYE agar plate preinoculated with a ring of mCherry‐expressing Legionella pneumophila ( Legionella 'wall'). The spread of the amoebae on the plate was assessed using a fluorescence imaging system or scanning electron microscopy. As a result, in contrast to the aposymbiotic amoebae, the symbiotic amoebae backpacked these GFP‐expressing bacteria and formed flower‐like fluorescence patterns in an anticlockwise direction. Other bacteria ( Pseudomonas aeruginosa and Stenotrophomonas maltophilia ), but not Staphylococcus aureus, were also backpacked by the symbiotic amoebae on LB agar, although lacked the movement to anticlockwise direction. Furthermore, in contrast to the aposymbiotic amoebae, the symbiotic amoebae backpacking the E. coli broke through the Legionella 'wall' on B‐CYE agar plates. Thus, we concluded that Acanthamoeba S13WT required the Neochlamydia endosymbiont to backpack human pathogenic bacteria and resist Legionella infection on solid agar.